The Relationship Between Duolingo Usage Intensity as Reinforcement and Vocabulary Mastery and Learning Motivation of Junior High School Students - Fadly Uzzaki; Zuwirna; Jasrial; Rahmi Pratiwi (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to evaluate the effectiveness of Duolingo as a reinforcement activity and analyze the relationship between objective and subjective usage intensity, vocabulary mastery, and learning motivation. Utilizing a quantitative approach with a correlational design, data was collected from 21 Junior High School students selected via purposive sampling. The instruments included digital logs from Duolingo for Schools, pretest-posttest vocabulary assessments, and questionnaires, which were analyzed using the Wilcoxon Signed Rank Test and Spearman Rank Correlation. The results demonstrated a significant increase in vocabulary mastery, achieving a medium N-Gain of 0.29, alongside high, predominantly intrinsic learning motivation with a mean score of 3.48. However, the discussion reveals a distinct "intention-behavior gap," showing a discrepancy between students' perceived subjective intensity and their actual objective usage logs. Furthermore, statistical analysis indicated no significant linear correlation between the duration of use and the improvements in vocabulary or motivation. In conclusion, while Duolingo serves as an effective structured reinforcement tool to enhance engagement and foundational vocabulary, the duration of app usage alone does not determine success, thereby highlighting an "illusion of productivity" within self-directed mobile learning.